PEMANFAATAN BIG DATA DALAM MENINGKATKAN LITERASI DIGITAL SISWA MELALUI PEMBELAJARAN E-LEARNING - Eko Giono; Jasiah Jasiah (JOURNAL SAINS STUDENT RESEARCH, 2025)
In this era of Revolution 4.0, technological advances have experienced rapiddevelopment, marked by the emergence of various new discoveries, one ofwhich is BigData. Big Data is defined as a very large collection of information. The presenceof BigData plays an important role in helping individuals explore the internet.The method used in this study is a literature review or narrative review. Data andinformation sources are collected from various available materials, such documents,articles, and books. The purpose of this study is to understand the use of bigdata inimproving students' digital literacy through online learning systems or e-learning.The results of the study show that Big Data can indirectly contribute to improving thequality of students' digital literacy. However, the use of this technology also faceschallenges, especially for students and educators in remote areas who have limited access to adequate technology. Big Data has a role in facilitating access to informationon the internet, as well as storing large volumes of material, media, and learning modeldata. E-learning functions as a bridge for students in utilizing technology effectively